Portrait of the exiled intellectual. Edward Said and critical thinking education - Gianluca Giachery (University of Bologna, 2022)
Edward Said was a versatile intellectual, anchored in a solid humanistic culture, who, in his career as a public figure as a university Professor at Columbia (N.Y.), placed at the center of his reflections the sense of commitment of the man of culture. His multifaceted education and his interests (from literature to politics, to music, up to the problems of teaching) are the summit of an attention to the generative issues of pedagogical and educational culture, aimed at redefining a new "radical humanism." For Said, however, the commitment and careful examination of texts and reality can only pass through an effort of critical thinking, capable of acquiring its own autonomy of judgment and, for this reason, point out and highlight the differences of all forms of power and coercion.